2021
DOI: 10.3390/jcm10040705
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Pharmacological and Surgical Treatment of Diabetes in Patients with Diabetic Retinopathy—A Review

Abstract: Background. Diabetes mellitus (DM) is a non-infectious pandemic of the modern world; it is estimated that in 2045 it will affect 10% of the world’s population. As the prevalence of diabetes increases, the problem of its complications, including diabetic retinopathy (DR), grows. DR is a highly specific neurovascular complication of diabetes that occurs in more than one third of DM patients and accounts for 80% of complete vision loss cases in the diabetic population. We are currently witnessing many groundbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 128 publications
(125 reference statements)
0
9
0
Order By: Relevance
“…A review by Matuszewski et al showed that rapid decline in glycaemia would lead to the occurrence and development of DR. The risk of DR was the highest when DM patients were treated with sulfonylurea and insulin, and the lowest when the patients were treated using SGLT-2i, GLP-1RA and dipeptidyl-peptidase-4 inhibitor (DPP-4i) ( 80 ). The different mechanisms employed by different drugs to lower blood glucose levels may account for their different effects on retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Matuszewski et al showed that rapid decline in glycaemia would lead to the occurrence and development of DR. The risk of DR was the highest when DM patients were treated with sulfonylurea and insulin, and the lowest when the patients were treated using SGLT-2i, GLP-1RA and dipeptidyl-peptidase-4 inhibitor (DPP-4i) ( 80 ). The different mechanisms employed by different drugs to lower blood glucose levels may account for their different effects on retinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic retinopathy (DR) is a diabetes-specific complication that occurs in more than one-third of patients and accounts for 80% of cases of total vision loss in the diabetic population [ 42 ]. Paradoxically, an excessively rapid fall in blood glucose is a risk factor for the onset and progression of DR.…”
Section: Resultsmentioning
confidence: 99%
“…Paradoxically, an excessively rapid fall in blood glucose is a risk factor for the onset and progression of DR. The highest risk is associated with the use of insulin or sulphonylureas, whereas SGLT2i are considered safe in this respect [ 42 ]. In a meta-analysis of 37 clinical trials that looked at the risk of DR with different hypoglycaemic agents in 100,928 patients with T2DM, SGLT2i were not associated with an increased risk of DR compared to placebo [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…When the scale is scored, positive items are scored in reverse. The sum of the four positively expressed items (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) provides the positive evaluation sub-dimension while the sum of 16 negatively expressed items (16-80) provides the negative evaluation sub-dimension. Total scale score is obtained by adding the 16 items with negative expressions and the four items with positive expressions after they are reversed.…”
Section: Data Collectionmentioning
confidence: 99%
“…[8] Studies have shown that insulin therapy is effective in slowing down the development and progression of chronic complications of diabetes. [9,10] More than half of patients with type 2 diabetes need insulin therapy after 5 years. Despite the importance of insulin therapy, many patients with type 2 diabetes are unwilling or afraid of insulin therapy.…”
Section: Introductionmentioning
confidence: 99%